Advertisement calls of the lesser spiny frog Quasipaa exilispinosa (Liu and Hu, 1975) (Anura: Dicroglossidae) - Chen, Zhi-Qiang; Hu, Hua-Li; Zhong, Jun-Jie; Shangguan, Hai-Ping (Zootaxa, 2021)
There are currently only eleven species of Quasipaa (Anura: Dicroglossidae) distributed in southern and southwestern China to central Vietnam, southeastern Thailand, and southwestern Cambodia and presumably also in Laos (Frost 2020). Eight species of Quasipaa are currently known in China: Q. boulengeri (Günther 1889), Q. courtoisi (Angel 1922), Q. exilispinosa (Liu & Hu 1975), Q. jiulongensis (Huang & Liu 1985), Q. shini (Ahl 1930), Q. spinosa (David 1875), Q. yei (Chen, Qu, and Jiang 2002), and Q. verrucospinosa (Bourret 1937). The first seven species are endemic to China (AmphibiaChina 2020). These species have similar morphological traits and are capable of introgressive hybridization between the closely related species of this genus(Zhang et al. 2018). Despite the detailed acoustic analysis that is available to identify a variety of species and is beneficial to the study of anuran taxonomy (e.g., Microhyla species; Chen et al. 2020), advertisement calls have only been reported in detail for Q. spinosa (Yu & Zheng 2009; Chen et al. 2012; Shen et al. 2015) and Q. shini (Kong et al. 2016), whereas the call for Q. exilispinosa was briefly described from observations in captivity (Voitel 2000).